Rancang Bangun Prototipe Sistem Pemantauan dan Kontrol Utilitas Gedung Berbasis PLC SCADA - Tugino; M. Arsyad; Sudiana; Bagas Nur Susanto; Yahya Ginanjar Endriawan; Sigit Budi Hartono (ReTII, 2025)
The use of PLC and SCADA enables real-time monitoring and control systems that are expected to improve operational efficiency and optimize energy use. This research aims to design and implement a PLC-SCADA-based monitoring system for high-rise building utilities such as generators, fire detection, lighting, air conditioning, and water supply. This research contributes to innovation in building technology and provides practical benefits in the use of high-rise building utilities more efficiently and safely. The research method includes the design of hardware and software that are connected simultaneously with the building infrastructure. Several sensors are used to detect the performance and damage of the high-rise building utilities, then the SCADA system will monitor and control the high-rise building utilities if problems occur remotely. The results show that the prototype device can monitor real-time of energy use, lighting, room temperature and humidity, alarm in case of fire, and the system’s reaction to changes in conditions that occur.